Pembiayaan Dana Pihak Ketiga Pada Pertumbuhan Laba Bersih Bank BNI Syariah - Wiwin Winarsih (Al-Urban: Jurnal Ekonomi Syariah dan Filantropi Islam, 2017)
The report to review the influence of financing growth,and third party funds to net profit growth syariah commercial banks. In this research using methods of correlational. Variables researched is growth financing and third party as variable indevenden and growth net profit as variabel devenden. Bank BNI Syariah research into population. Sampling technic using sample purposive sampling and 36 report monthly financial Bank BNI Syariah as sanples. Data collection technic ques used by using review of documents. Processing technic ques and analysis of data used in analysis accounting and linier regression analysis worship of idols. The result of variable of financing have an insignificant effect to net profit, while third party fund variable have positive and significant influence to net profit.